Chemical polymorphism of the essential oils from populations of Thymus caespititius grown on the islands Pico, Faial and Graciosa (Azores) - Pereira, S. I. (2003)
The compositions of the essential oils isolated from the aerial parts of 11 populations of Thymus caespititius collected during the flowering phase on Pico, Faial and Graciosa (Azores) were studied by GC and GC-MS. The monoterpene fraction was dominant in all the oils analysed (55-90%) and consisted mainly of oxygen-containing compounds (44-79%). Sesquiterpenes represented an important fraction of the oils from the populations grown on Graciosa (13-28%). In contrast, this fraction was rather small in the oils from the populations grown on Pico and Faial (6-11%). Despite this, oxygen-containing compounds (4-18%) were always dominant. Cluster analysis of all identified oil components grouped the oils into three main clusters that corresponded with their main components. The oils from the 11 populations studied showed a clear chemical polymorphism that, in some cases, was more evident among populations growing on the same island than among those from different islands. Copyright © 2003 John Wiley & Sons, Ltd.